Exploring the denaturation of whey proteins upon application of moderate electric fields : a kinetic and thermodynamic study - Pereira, Ricardo (2011)
Thermal processing often results in disruption of the native conformation of whey proteins, thus affecting functional properties. The aim of this work was to evaluate the effects of moderate electric fields on denaturation kinetics and thermodynamic properties of whey protein dispersions at temperatures ranging from 75 to 90 °C. Application of electric fields led to a lower denaturation of whey proteins, kinetically traduced by lower values of reaction order (n) and rate constant (k) (p < 0.05), when compared to those from conventional heating under equivalent heating rates and holding times. Furthermore, the application of electric fields combined with short come-up times has reduced considerably the denaturation of proteins during early stages of heating (>30% of native soluble protein than conventional heating) and has determined also considerable changes in calculated thermodynamic properties (such as Ea, ΔH, ΔS). In general, denaturation reactions during moderate electric fields processing were less dependent on temperature increase.